Stainless Steels and Alloys - Duriagina, Zoia (IntechOpen, 2019)
Materials science is the magic that allows us to change the chemical composition and microstructure of material to regulate its corrosion-mechanical, technological, and functional properties. Five major classes of stainless steels are widely used: ferritic, austenitic, martensitic, duplex, and precipitation hardening. Austenitic stainless steels are extensively used for service down to as low as the temperature of liquid helium (-269ºC). This is largely due to the lack of a clearly defined transition from ductile to brittle fracture in impact toughness testing. Steels with ferritic or martensitic structures show a sudden change from ductile (safe) to brittle (unsafe) fracture over a small temperature difference. Even the best of these steels shows this behavior at temperatures higher than -100ºC and in many cases only just below zero. Various types of stainless steel are used across the whole temperature range from ambient to 1100ºC. This book will be useful to scientists, engineers, masters, graduate students, and students. I hope readers will enjoy this book and that it will serve to create new materials with unique properties.